Smart monitoring system using Internet of Things: Application for agricultural management in Benin - HOUNGUE, Yénukunmè Pélagie Elyse; DAHOUE, Gilles; KOMACLO, Julien (My University, 2022)
One of the major tools of the new era of digital transformation is Internet of Things (IoT) through which, one can look forward to exploring the new technologies in the digital world as well as how they help in improving the real world. This work provides an overview of the approach used to deploy a surveillance system for monitoring any indoor space in general and specifically for agricultural spaces. The entire process starts after motion detection by motion sensors using Machine Learning techniques. This requires coverage and response processing algorithms implemented in the electronic chain. The electronic part of the system relies on the microcontrollers, sensors and communications between them. A mobile application has been developed to allow competent authorities to receive alerts for real-time intervention with the aim of preventing the destruction of crops slaughtered near herds passage. The monitoring system’ synoptic diagram and its operation along with the power modules description are introduced. Prototype has been designed and performance evaluation performed to show the system’ responsiveness.
Keywords: Monitoring system; agricultural space; machine; learning; herds passage; motion detection.